Value of microwave ablation in treatment of large lesions of hepatocellular carcinoma. Issue 8 (10th September 2015) - Medhat, Eman; Abdel Aziz, Ashraf; Nabeel, Mohammed; Elbaz, Tamer; Zakaria, Zeinab; Shousha, Hend; Amer, Ayman; Fouad Fathalah, Waleed; Maher, Rabab; Musa, Shereif
<x xml:space="preserve">Abstract</x> Objective Thermal ablative therapies continue to be favored as a safe and effective treatment for patients with non‐resectable hepatocellular carcinoma (HCC). Percutaneous microwave ablative therapy, which is a relatively new technique, has the advantage in providing faster ablation of large tumors. This study aimed to evaluate microwave ablation in the treatment of large HCC (5–7 cm) and to assess its effect on local tumor progression, prognostic outcome and patients' survival. Methods In all, 26 patients with large HCC lesions (5–7 cm) were managed in the multidisciplinary clinic of Kasr Al Ainy University hospital using microwave ablation. The treatment was performed with the patient under conscious sedation and analgesia and ultrasonography‐guided using an HS AMICA microwave machine operating at frequency of 2450 MHz and a power up to 100 W. Multiple needle insertions were made in one or two sessions according to the size of the lesion. The complete ablation rate, local tumor progression and patients' overall survival were analyzed, and the efficacy and safety of MWA was evaluated. Results Complete ablation was achieved in 19/26 (73.1%). Local tumor progression was recorded in five treated lesions (19.2%). Distant tumor progression within the liver was recorded in six patients (23.1%), with a mean survival of 21.5 months. No procedure‐related major complications or deaths were observed. Conclusions Percutaneous microwave ablation is safe and effective in the treatment of large HCC tumors. Patients' survival and local tumor control were acceptable.